2023
DOI: 10.1017/s0950268823000092
|View full text |Cite
|
Sign up to set email alerts
|

Use of portable air purifiers to reduce aerosols in hospital settings and cut down the clinical backlog

Abstract: SARS-CoV-2 has severely affected capacity in the NHS, and waiting lists are markedly increasing due to downtime of up to 50 minutes between patient consultations/procedures, to reduce the risk of infection. Ventilation accelerates this air cleaning, but retroactively installing built-in mechanical ventilation is often cost-prohibitive. We investigated the effect of using portable air cleaners (PAC), a low-energy and low-cost alternative, to reduce the concentration of aerosols in typical patient consultation/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…One study suggested that air ventilation (open windows) alone was unable to reduce concentrations back to baseline levels without the aid of an AFU, with the ‘windows open, AFU on’ condition producing the lowest concentrations and highest clearance rate of PM2.5 (Fennelly et al, 2022). Salmonsmith et al (2023) reported that PAC mitigation is very effective in clearing the air of aerosols in rooms, this could also reduce the half-life aerosols by 82%, Gola et al (2020) also found that filtration units reduced local airborne loads and suggested they should be used in hard functional areas such as ICUs. As Rezaei et al (2020) looked at cleaning rooms, they identified that a HVAC system provided exhaust air ranging from 50-80 degrees Celsius and with 40-50% humidity, under these conditions COVID-19 was observed to rapidly disappear improving infection control across whole hospitals.…”
Section: Rq1 and Rq3mentioning
confidence: 99%
“…One study suggested that air ventilation (open windows) alone was unable to reduce concentrations back to baseline levels without the aid of an AFU, with the ‘windows open, AFU on’ condition producing the lowest concentrations and highest clearance rate of PM2.5 (Fennelly et al, 2022). Salmonsmith et al (2023) reported that PAC mitigation is very effective in clearing the air of aerosols in rooms, this could also reduce the half-life aerosols by 82%, Gola et al (2020) also found that filtration units reduced local airborne loads and suggested they should be used in hard functional areas such as ICUs. As Rezaei et al (2020) looked at cleaning rooms, they identified that a HVAC system provided exhaust air ranging from 50-80 degrees Celsius and with 40-50% humidity, under these conditions COVID-19 was observed to rapidly disappear improving infection control across whole hospitals.…”
Section: Rq1 and Rq3mentioning
confidence: 99%
“…67,[72][73][74]83 Under this category, 11 studies investigated the use of personal or localized ventilation units. [85][86][87][88][89][90][91][92][93][94][95] The remaining eight discussed the use of air purifiers and air cleaners with a high-efficiency particulate air (HEPA) filter [96][97][98][99][100][101][102][103] to minimize exposure to infectious aerosols. These experimental studies showed that add-on portable ventilation devices could effectively contain and remove aerosolized particles.…”
Section: Abstract Co-occurrencementioning
confidence: 99%
“…Reading the article titled ‘Use of portable air purifiers to reduce aerosols in hospital settings and cut down the clinical backlog’ by Jacob Salmonsmith et al [ 1 ] encouraged us to publish a commentary on the extrapolated conclusions regarding the use of portable air cleaners to reduce the concentration of aerosols in patient environments. We hope these perspectives may provide insight into areas that may require further research and improvement.…”
mentioning
confidence: 99%
“…In the aforementioned article, the authors summarised that the onset of the Covid-19 virus saw a substantial increase in the patient waiting lists for doctor consultations and procedures in healthcare settings in order to decrease disease transmission [ 1 ]. The researchers proposed that portable air cleaners (PACs) can be a cost-effective alternative to built-in mechanical ventilation systems to reduce potentially infectious aerosol concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation